Experimental Investigation on Strength Appearances of M35 and M40 Grades of Concrete Using Curing Compound - Chandra Sekhar Malla, Mithun Reddy P, Mukunda Rao D, Bose Boppana (International Journal of Advanced Science and Technology, 2019)
Nanomaterials have extraordinary physical and synthetic qualities, which would work on the design and would likewise cause a few varieties in the structures of the right now existing materials. The reason why Nano-silica is chosen instead of micro-silica in this project is that the pozzolanic movement of the Nano-silica particles is particularly more than that of the Miniature Silica because of the impressively high surface to volume proportion. Utilization of Portland Concrete gives high strength and sturdiness to structures in view of its ideal molecule size conveyance and unrivaled solidified structure. Nano silica is the material which shows valuable impact in the process of accumulative strength and stability of the structure. In the current work, Nano silica is utilized as a fractional substitution for Concrete by weight and PEG400 as self-curing agent. In this work strength studies are conducted on M35 and M40 Grade concrete with Nano Silica by comparing them with PEG400 and without PEG400. Ordinary Portland cement was used in this work. Nano silica is utilized as a fractional substitution to Ordinary Portland binder by 1.5% of total binder weight. Strength concentrates like Pressure Strength, Split elasticity and flexural strength were directed on M35 and M40 grade concrete including and omitting PEG400. In the present work partial replacement of Nano silica to cement showed a good influence in increasing strength properties. Use of PEG400 as self-curing agent attained 90% of strengths while compared without PEG400.